The impact of apiculture on the structure of Atlantic island honey bee populations - Muñoz, Irene (2013)
Beekeeping practices such as importation of non-native honeybee queens may interact with the conservation of honey bee subspecies and ecotypes biodiversity. Island honey bee populations are especially appropriate to test the impact of the introduction of foreign subspecies into their genetic diversity and structure. Here we used microsatellite markers to test whether genetic introgression from introduced honey bee queens is taken place in the honey bee populations from the Canary Islands, Azores and Madeira (Macaronesian region). We found introgression signals from foreign honeybee populations on Atlantic islands based on Bayesian structure analysis and Hardy-Weinberg equilibrium test. Fst pairwise comparisons with Iberian, North African and other European populations and structure analyses suggest different sources of honey bee queens into the islands: while honey bees from Canary Islands showed introgression from European honey bees, the honey bees from Azores and Madeira showed a closer relationship with those from the Iberian Peninsula. The existence of endemic honey bee populations on the Canary Islands prone to be conserved can still be depicted from the aforementioned analyses.